2021
DOI: 10.1111/beer.12366
|View full text |Cite
|
Sign up to set email alerts
|

Promoting employees’ pro‐environmental behaviour through empowering leadership: The roles of psychological ownership, empowerment role identity, and environmental self‐identity

Abstract: This study develops a theoretical model to investigate when and why empowering leadership promotes employees’ pro‐environmental behaviour (PEB). Synthesising psychological ownership theory and role identity theory, we propose that empowering leadership positively affects the employees’ PEB and that this relationship is mediated by psychological ownership. Furthermore, we examine the moderating roles of empowerment role identity and environmental self‐identity in this relationship. By employing 203 leader–follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 88 publications
1
32
0
Order By: Relevance
“…According to Bandura and Hall (2018) , direct and indirect interactions can help employees develop a sense of accountability, such as seeing ethical leaders holding individuals responsible for their accomplishments as well as the method by which those successes were obtained. The norms for social conduct in the organization were established based on observations and interactions between employees ( Cheng et al, 2021 ). In addition, employees are held responsible for their own actions ( Podsakoff et al, 2003 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…According to Bandura and Hall (2018) , direct and indirect interactions can help employees develop a sense of accountability, such as seeing ethical leaders holding individuals responsible for their accomplishments as well as the method by which those successes were obtained. The norms for social conduct in the organization were established based on observations and interactions between employees ( Cheng et al, 2021 ). In addition, employees are held responsible for their own actions ( Podsakoff et al, 2003 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Some studies have conceptualized the four categories of psychological ownership as self-identity, self-efficacy, belongingness, and accountability ( Pierce et al, 2001 , 2003 ; Avey et al, 2009 ). The sense of psychological ownership toward organization make employees more proactive, caring, and attached to the organization with the sagacity of responsibility ( Cheng et al, 2021 ). The responsible leadership style is based upon stakeholder relations and ethical consideration.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Similarly, the sense of commitment can also be incurred by the feeling of ownership and organizational support, facilitating employees to engage in innovation in the workplace ( Liu F. et al, 2019 ). With a feeling of psychological ownership, employees become more attached to, protective of, and responsible for their organizations ( Pierce et al, 2001 , 2003 ; Van Dyne and Pierce, 2004 ; Liu et al, 2012 ), leading to a series of positive impacts on employees, for example, caring more about organizational innovation and improving work efficiency through hard work and innovative behavior ( Wagner et al, 2003 ; Cheng et al, 2021 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Employees feel psychologically intertwined with their organizations and spontaneously internalize innovation as their own goals. The sense of psychological ownership often induces satisfaction with their job ( Schulte et al, 2006 ; Avey et al, 2012 ) and is accompanied by a sense of responsibility, proactiveness, and organization-based self-esteem ( Liu et al, 2012 ; Cheng et al, 2021 ) to seek creative solutions to problems and foster innovation behavior accordingly ( Liu F. et al, 2019 ; Leyer et al, 2021 ). Meanwhile, prior studies have shown that the organizational innovation climate fulfills the employees’ needs for a sense of belonging ( Hammond et al, 2011 ; Übius et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%